Joint associations between neighborhood walkability, greenness, and particulate air pollution on cardiovascular mortality among adults with a history of stroke or acute myocardial infarction. Issue 2 (18th April 2022) - Liao, Noelle S.; Van Den Eeden, Stephen K.; Sidney, Stephen; Deosaransingh, Kamala; Schwartz, Joel; Uong, Stephen P.; Alexeeff, Stacey E.
Abstract : Background: Fine particulate matter (PM2.5 ) is a known risk factor for cardiovascular disease (CVD). Neighborhood walkability and greenness may also be associated with CVD, but there is limited evidence on their joint or interacting effects with PM2.5 . Methods: Cox proportional hazard models were used to estimate the risk of CVD mortality among adults with a history of acute myocardial infarction and/or stroke living in Northern California. We assessed the independent and joint effects of walkability, greenness (Normalized Differentiated Vegetation Index [NDVI]), and PM2.5 at residential addresses, controlling for age, sex, race/ethnicity, comorbidities, BMI, smoking, revascularization, medications, and socioeconomic status. Results: Greenness had a nonlinear association with CVD mortality ( P = 0.038), with notably protective effects (HR = 0.87 [95% confidence interval CI = 0.78, 0.97]) at higher greenness levels (NDVI ≥ 0.3) and moderate attenuation after adjusting for PM2.5 (HR = 0.92 [95% CI = 0.82, 1.03]) per 0.1 increase in NDVI. Walkability had no independent effect on CVD mortality. PM2.5 had a strong independent effect in models adjusted for greenness and walkability (HR = 1.20 [95% CI = 1.08, 1.33)) per 10 μg/m 3 increase in PM2.5 . There was an interaction between walkability and PM2.5 ( P = 0.037), where PM2.5 had slightly stronger associations in more walkable than less walkable neighborhoods (HR = 1.23 [95% CI = 1.06, 1.42] vs. 1.17 [95% CI = 1.04, 1.32]) per 10 μg/m 3 increase in PM2.5 . Greenness had no interaction with PM2.5 ( P = 0.768) nor walkability ( P = 0.385). Conclusions: High greenness may be protective of CVD mortality among adults with CVD history. PM2.5 associated CVD mortality risk varies slightly by level of neighborhood walkability, though these small differences may not be clinically meaningful.